Tindakan Sosial Aktor dan Dinamikanya pada Sistem Sosial: Studi Kasus Usaha Arang Tradisional dalam Penghidupan Komunitas Suku Akit - Yuliana, Dhina; A. Kinseng, Rilus; Hadi Dharmawan, Arya; Soetarto, Endriatmo (Sodality: Jurnal Sosiologi Pedesaan, 2022)
The Akit community generally uses mangrove wood as raw material for charcoal. The purpose of this study was to analyze (a) the development of the charcoal-making business, (b) the type of social action in the Akit community's charcoal-making business, and (c) the dynamics of the charcoal-making business. This research was conducted using an ethnographic approach. The results: from the 1980s to 1994, production was initially regulated solely to meet local needs. In the era of 1995 to 2005, it experienced a high market demand for mangrove charcoal along with a flourishing business network with Malaysian toke. After 2005 the charcoal business dimmed again due to government regulations. The actors involved in the charcoal business are workers, owners of very small panglongs, and owners of small panglongs (tokes). The social action run the panglong business as an effort to meet their family needs, and thus they worked based on instrumental rationality. These charcoal-making entrepreneurs operated their businesses based on instrumental and traditional actions. The social action of the toke actor is instrumental rationality and value-oriented rationality. The dynamics of the charcoal business in the Akit community have experienced ups and downs.